Curcumin inhibits urothelial tumor development by suppressing IGF2 and IGF2-mediated PI3K/AKT/mTOR signaling pathway. (9th August 2017) - Tian, Binqiang; Zhao, Yingmei; Liang, Tao; Ye, Xuxiao; Li, Zuowei; Yan, Dongliang; Fu, Qiang; Li, Yonghui
Abstract: We have previously reported that curcumin inhibits urothelial tumor development in a rat bladder carcinogenesis model. In this study, we report that curcumin inhibits urothelial tumor development by suppressing IGF2 and IGF2-mediated PI3K/AKT/mTOR signaling pathway. Curcumin inhibits IGF2 expression at the transcriptional level and decreases the phosphorylation levels of IGF1R and IRS-1 in bladder cancer cells and N -methyl- N -nitrosourea (MNU)-induced urothelial tumor tissue. Ectopic expression of IGF2 and IGF1R, but not IGF1, in bladder cancer cells restored this process, suggesting that IGF2 is a target of curcumin. Moreover, introduction of constitutively active AKT1 abolished the inhibitory effect of curcumin on cell proliferation, migration, and restored the phosphorylation levels of 4E-BP1 and S6K1, suggesting that curcumin functions via suppressing IGF2-mediated AKT/mTOR signaling pathway. In summary, our results reveal that suppressing IGF2 and IGF2-mediated PI3K/AKT/mTOR signaling pathway is one of the mechanisms of action of curcumin. Our findings suggest a new therapeutic strategy against human bladder cancer caused by aberrant activation of IGF2, which are useful for translational application of curcumin.